GAMBARAN PENGETAHUAN IBU MENGENAI TANDA KEGAWATAN DIARE DAN PENANGANAN AWAL DI RUMAH PADA BALITA - Nuraini Hakim; Febriana (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Almost all age groups are affected by diarrhea, especially children under five years old because they still do not have optimal immune systems. Complications that directly arise from diarrhea are dehydration, loss of fluids and electrolytes, organ damage, and even coma. This research aims to determine the description of mothers' knowledge regarding signs of emergency diarrhea and initial treatment at home for children under five at home. This research design uses descriptive to describe a person's level of knowledge and uses a questionnaire instrument. The research results obtained from 105 respondents showed that 13.3% had poor knowledge, 12.4% had good knowledge, and 74.3% had sufficient knowledge. This explains that the majority of respondents have quite good knowledge about the signs of emergency diarrhea and initial treatment at home. Recommendations for the family are to give oral rehydration solutions to children with diarrhea to prevent dehydration, and for health services to provide regular health education, especially regarding diarrhea and administering oral rehydration solutions at home